UNDERSTANDING THE SOCIAL DETERMINANTS OF INTELLECTUAL DISABILITIES: A COMPREHENSIVE REVIEW: - Naresh Kumar Jaiswal (Universitas Efarina, 2023)
Intellectual disabilities (ID) are a complex and heterogeneous group of disorders characterized by limitations in intellectual functioning and adaptive behavior. While biological factors are critical in understanding ID, the role of social determinants cannot be overstated. This paper provides a comprehensive review of the social determinants influencing the prevalence, diagnosis, treatment, and outcomes of intellectual disabilities. It synthesizes existing research to highlight how socioeconomic status, education, access to healthcare, cultural factors, and environmental influences shape the experiences of individuals with ID and their families. By understanding these social determinants, stakeholders can develop more effective strategies to support and empower individuals affected by intellectual disabilities.